Pastoral Theology : Theological Foundations for Who a Pastor is and What He Does - Akin, Daniel L.; Pace, R. Scott (Nashville : B&H Academic, 2017)
Pastoral Theology constructs a theological framework for pastoral ministry that is biblically derived, historically informed, doctrinally sound, missionally engaged, and contextually relevant.
Vendor-supplied metadata.
Added to collection customer.56279.3
Keywords: Pastoral theology; Pastoral theology; Electronic books